A clear view: crowdsourcing conservation needs in historic houses using visitor-led photo surveys. (4th March 2019) - Dillon, C.; Golfomitsou, S.; Storey, C.; Lithgow, K.
ABSTRACT: In order to investigate visitor perceptions of dust, dirt and cleaning in historic houses, visitors were invited to be a 'researcher' for the day at an historic house and photograph what they felt to be a conservation need. This self-directed photo survey provided a useful communication tool between visitors, researchers, conservators and collection care staff. The method generated specific and actionable feedback about the focus of visitors' attention, their perception of risk in the historic environment and the impact of conservation plans on the visitor experience. Although the non-expert nature of visitors' observations was clear, there was new insight into what visitors find attractive, alarming or anomalous in a historic house environment. This accessible and inclusive method is potentially easily conducted by staff and volunteers involved in collections care. The results could be used to inform training, prioritisation, presentation and interpretation, as well as conservation.